2021
DOI: 10.1111/ocr.12464
|View full text |Cite
|
Sign up to set email alerts
|

Incisive canal remodelling following maximum anterior retraction reduces apical root resorption

Abstract: Maximum retraction of the anterior teeth with premolar extraction is necessary to improve occlusion and facial aesthetics in patients with lip protrusion or severe skeletal/dental discrepancies. The application of temporary anchorage devices (TADs) has improved the efficiency and the predictability of 3-dimensional management of tooth movement and anchorage control; thus, incorporating TADs in comprehensive treatment, especially for premolar extraction cases, is well-accepted in clinical orthodontics. 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 22 publications
2
12
1
Order By: Relevance
“…A recent clinical study 12 had significant and shocking results, in which 53% of the cases that underwent maximum retraction showed IC invasion with grade 3 root resorption. The amount of root resorption was significantly higher with IC invasion than without invasion (2.39 mm vs 0.82 mm, P , .0001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent clinical study 12 had significant and shocking results, in which 53% of the cases that underwent maximum retraction showed IC invasion with grade 3 root resorption. The amount of root resorption was significantly higher with IC invasion than without invasion (2.39 mm vs 0.82 mm, P , .0001).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, different degrees of root resorption were observed with an average of 2.39 mm, and the largest degree of invasion demonstrated 6.2 mm of root resorption. 12 ''The safety zone'' of orthodontic retraction may be less than traditionally thought. Most previous studies 11,13 identified the IC opening (incisive foramen) as the lowest point of the IC palatal wall rather than the buccal wall, which was presented in the study by Pan and Chen.…”
Section: Introductionmentioning
confidence: 99%
“…As previously reported [ 41 ], those morphometric parameters could be of clinical relevance for the interventions in the anterior maxilla, such as implant placement. However, morphometric analyses, such as those performed in this study, could also influence other clinical aspects, since it has been shown that the increase in NPC width (M-L IF) was accompanied by higher prevalence of NPC perforation during maximum central incisors retraction [ 20 , 22 ]. Furthermore, the enhancement of ML-IF diameter can also be addressed for subsequent complications, such as orthodontically induced inflammatory root resorption [ 12 , 27 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, it seems that the increase in M-L IF, A-P IF, A-P NF, and NPC length in funnel-shaped NPC may be a risk factor for the interventions that could result in teeth movement. Literature data offer only the evidence that M-L diameter (NPC width) may contribute to adverse events accompanying orthodontic procedures [ 22 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation